Infrared radiofluorescence (IR-RF) dating: a review - Murari, Madhav Krishna; Kreutzer, Sebastian; King, Georgina; Frouin, Marine; Tsukamoto, Sumiko; Schmidt, Christoph; Lauer, Tobias; Klasen, Nicole; Richter, Daniel; Friedrich, Johannes; Mercier, Norbert; Fuchs, Markus (Quaternary geochronology, 2021)
Luminescence dating methods on natural minerals such as quartz and feldspars are indispensable for establishing chronologies in Quaternary Science. Commonly applied sediment dating methods are optically stimulated luminescence (OSL) and infrared stimulated luminescence (IRSL). In 1999, Trautmann et al. (1999a, b) proposed a new related technique called infrared radiofluorescence (IR-RF). IR-RF denotes the infrared luminescence signal of feldspar resulting from exposure to ionizing radiation and potentially offers a significant methodological advance compared to OSL and IRSL regarding luminescence signal stability, dating range and required measurement time. The method has rarely been applied due to a lack of commercially available measurement equipment but experienced a revival during the last years. The present article provides a state-of-the-art overview of the physical background of IR-RF, its challenges, applications and the potential as a dating method. The paper particularly addresses practical considerations for applying IR-RF dating, including signal bleachability and saturation behaviour, and summarizes proposed solutions.